Should Contralateral Nodules Be an Indication of Total or Completion Thyroidectomy for Patients With Unilateral Papillary Thyroid Carcinoma? - Ma, Tengfei; Wang, Haiyang; Liu, Jifeng; Zou, Jian; Liu, Shixi (Frontiers in Endocrinology, 2021)
Objective To determine whether papillary thyroid carcinoma (PTC) patients with benign or nonsuspicious nodules in the contralateral lobe have a higher rate of recurrence or worse survival after lobectomy compared to those without nodules in the contralateral lobe. Methods Adult patients who underwent lobectomy and were diagnosed with unilateral PTC (2013-2015), were identified from an institutional database. Patients who previously had cytologically benign nodules or nonsuspicious nodules in the contralateral lobe comprised the contralateral nodule (CN) group. Patients who did not have nodules in the contralateral lobe comprised the unilateral nodule (UN) group. Results 370 patients were included: 242 in the UN group and 128 in the CN group. After a median follow-up of 62 months (range, 16–85 months), recurrence was confirmed in 4.1% patients in the UN group and 5.5% patients in the CN group (p = 0.559). Clinical contralateral lobe PTC was detected in 2.9% (7/242) of patients from the UN group and 3.9% (5/128) of patients from the CN group (p = 0.601). The 5-year contralateral lobe recurrence-free survival (RFS) rates were 96.8% in the UN group and 97.4% in the CN group (p = 0.396). The 5-year loco-regional RFS rates were 98.4% in the UN group and 97.8% in the CN group (p = 0.690). The 5-year disease-specific survival rates were both 100%. Conclusion PTC patients with benign or nonsuspicious CNs have similar recurrence and survival rates after lobectomy compared to those without CNs. CNs alone should not be an indication for total or completion thyroidectomy.